ANALISIS PROSES STRATEGI INOVASI DARI PERSPEKTIF PENGEMBANGAN DIRI SEORANG ENTREPRENEUR (Studi pada UKM â€œCity Brandingâ€ di Malang Raya) - -, Rofiaty (Universitas Slamet Riyadi, 2015)
SMEs are business sector that is resilient to the turmoil of changes in environmental conditions, tough and can survive compared to large business and corporations, objective research to understand and analyze the innovation strategies of SMEs which constitute Malang city branding is based on the concept of self development in innovating. This study is a qualitative study, using the paradigm fenomology. The informants are Keripik Tempe Rohani in Malang, Petani Bunga and Pusat Makanan Oleh-oleh Vigor in Batu and Batik Druju in Malang. The research findings is the theme of legacy business, consumers and competitors theme, the theme of the income, while the conclusions are (1) the reasons that encourage SMEs to innovate is the legacy business, to anticipate consumer saturation and competition, and to increase revenue; and (2) the innovation strategy undertaken by SMEs. Keywords: process innovation strategy, the development of self entrepreneurs, SMEs